Exploring The Contribution of Mind Mapping-Based Constructivist Strategy on Fiqh Learning Outcomes - Ridwan (Nadwa: Jurnal Pendidikan Islam, 2023)
Improving fiqh learning outcomes requires empirically tested learning strategies following the characteristics of the material and learning. This study aims to examine (1) the effect of constructivist-based mind-mapping learning strategies on cognitive learning outcomes of fiqh subjects with intelligence control (intelligence) and (2) the influence of constructivist-based mind mapping learning strategies on cognitive learning outcomes of jurisprudence subjects with control of learning motivation. This research uses an experimental design carried out at MAN 1 Semarang City. Data were collected using tests (learning outcomes), questionnaires (learning motivation), and documentation (intelligence). Next, the collected data were analyzed using simple Variance Analysis (Anava) and Covariance Analysis (ANAKOVA) techniques. The results of data analysis found that constructivist-based mind-mapping learning strategies significantly influenced students' Fiqh learning outcomes after controlling their intelligence/intelligence and learning motivation. This shows that if the level of intelligence is the same, the Fiqh learning outcomes achieved by students who follow constructivist-based mind-mapping learning strategies are higher than those achieved by those who follow conventional learning strategies. Likewise, if motivation levels are the same, the jurisprudence learning outcomes of students who follow constructivist-based mind-mapping learning strategies are higher.